Lead like Walt : discover Walt Disney's magical approach to building successful organizations - Williams, Pat (Highbridge Audio, 2019)
Whether you are building a small business from the ground up or managing a multinational company, you can learn the seven key traits for leadership success from one of the greatest business innovators and creative thinkers of the twentieth century: Walt Disney. Whether you know him as the first to produce cartoons in Technicolor, the mastermind behind the theme park Disneyland, or the founder of the largest entertainment conglomerate, Walt's story of creativity, perseverance in spite of obstacles, and achieving goals resonates and inspires as much today as it ever has. Author Pat Williams began studying the life and leadership example of Walt Disney as he struggled to build an NBA franchise, the Orlando Magic. Since he was trying to accomplish a goal similar to so many of Walt's-starting with nothing and building a dream from the ground up-he realized that Walt could teach him what he needed to know. And indeed he did. Through Walt Disney's leadership example, Pat found seven key leadership traits that all great leaders must possess: Vision, Communication, People Skills, Character, Competence, Boldness, and A Serving Heart. Through never-before-heard Walt stories and pragmatic principles for exceeding business goals, you'll learn how to build those skills and implement them to be effective in any leadership arena.